How Local Art Reveals Local Genius In The Corner Of The Discourse Point of View - Riswani, Riswani; Efrinon, Efrinon; Alfalah, Alfalah; Firdaus, Firdaus; Jufri, Jufri (ppjbsip, 2023)
This study presents a comprehensive literature review on the discourse surrounding local genius in artistic practices within the context of Indonesia. The presence of highly diverse local geniuses, owned by various tribes across the archipelago, is a significant indicator of civilization in Indonesia, particularly in the region of West Sumatra. The significance of local genius is contingent upon its comprehension and admiration by individuals involved in its development, thereby transforming it into a source of community pride and fostering its conservation. If the local intellectual community is robust, there is no cause for concern regarding introducing external cultural elements that do not align with the Indonesian national identity. Indeed, individuals with exceptional intellectual abilities from foreign cultures can serve as catalysts or facilitators for nurturing indigenous genius in Indonesia.